Islam on the air: the struggle for salafism through radio in Indonesia - Masduki Masduki; Akh. Muzakki; Imron Rosidi; Toni Hartono (Indonesian Journal of Islam and Muslim Societies, 2022)
Indonesian Islam has become the point of contestation of ideologies, particularly between the so-called globally-inspired and locally- rooted views of Islam. This article deals with the Salafism struggle in da’wah on the airwaves through the radio as locally rooted in Indonesia with a special reference to the Salafi radio highly popular in Batam of Riau, Hang Radio. It analyzes two main issues, first on the growth of religious thinking in Indonesian Islam and its relationship with media propaganda, and second on the Salafi struggle for Islamic identity by means of broadcasting through radio. It argues that through the radio the Salafists implement their ideology as part of their socio-religious identity in a public sphere. Through a hermeneutical-phenomology analaysis, this article finds thatthe Salafism struggle of Islamic identity by means of radio is fragmented rather than cohesive and solid. Moreover, this struggle is not immune to capitalism. Above all, this struggle is also influenced by transnational and local elements.